PsycEXTRA Dataset 2006
DOI: 10.1037/e721222007-001
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury in the United States: Emergency Department Visits, Hospitalizations, and Deaths

Abstract: Highlights of the Results Each year in the United States: • At least 1.4 million people sustain a TBI. Of them, about 50,000 die, 235,000 are hospitalized, and 1.1 million are treated and released from an ED. Purpose of the Report Traumatic Brain Injury in the United States: Emergency Department Visits, Hospitalizations, and Deaths presents basic data on the incidence of TBI. It goes beyond previous reports by including ED visits, and answers a wide range of important questions about how many TBIs occur each y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
658
3
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 653 publications
(689 citation statements)
references
References 7 publications
(7 reference statements)
14
658
3
14
Order By: Relevance
“…In the United States alone, there are an estimated 475,000 annual cases of TBI among children under the age of 15 years, resulting in 2,685 deaths. 1 The disabilities resulting from pediatric TBI are often profound and life-long, 2 and include sensorimotor 3 and cognitive impairments 4 as well as psychological dysfunction. 4 TBI is defined as any head injury with traumatic etiology, including blunt or penetrating trauma and nonaccidental injury.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States alone, there are an estimated 475,000 annual cases of TBI among children under the age of 15 years, resulting in 2,685 deaths. 1 The disabilities resulting from pediatric TBI are often profound and life-long, 2 and include sensorimotor 3 and cognitive impairments 4 as well as psychological dysfunction. 4 TBI is defined as any head injury with traumatic etiology, including blunt or penetrating trauma and nonaccidental injury.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that falls are the most common cause of TBI in older adults since approximately 10% of falls in older people result in injuries such as TBI as per Thompson et al 31 . Other studies have confirmed that falls were the leading mechanism of TBI for older adults, accounting for 51% of cases as per Langlois et al 32 . But this is not consistent with our studies.…”
Section: Gender Distribution 1st Qtr 2nd Qtrmentioning
confidence: 64%
“…The Center for Disease Control (CDC) estimates that at least 1.4 million people sustain a TBI each year (Langlois, Rutland-Brown & Thomas, 2006). Brain injuries are more likely to result in death than any other type of injury, and TBI is the leading cause of long-term disability both in the United States and worldwide (North American Brain Injury Society, n.d.; Thurman et al, 1999) making TBI a significant public health concern.…”
Section: Prevalence Of Traumatic Brain Injury Prevalence In the Unitementioning
confidence: 99%
“…For example, head injury is 1.5 times more likely to affect men than women (CDC, 2006) Though the causes of the elevated TBI rate among incarcerated adults are not well understood, the evidence presented thus far clearly suggests that rates of TBI are significant in correctional populations. Knowledge and awareness of the incidence of TBI in the general population has increased over time as it has become a focus for research (Langlois et al, 2006). However, only one large-scale meta-analysis to date has attempted to determine the incidence of TBI among incarcerated populations.…”
Section: Prevalence In Incarcerated Populationsmentioning
confidence: 99%
See 1 more Smart Citation